An experimental evaluation of DoS attack and its impact on throughput of IEEE 802.11 wireless networks - Malekzadeh, Mina; Abdul Ghani, Abdul Azim; Desa, Jalil; Subramaniam, Shamala (2008)
a variety of locations. This has lead to development of high level security protocols for WLAN. The newest protocol IEEE 802.11i ratified to provide strong data encryption but it can not prevent Denial of Service (DoS) attacks on WLAN. This paper in a testbed, conducts an experimental framework to implement and quantify common types of DoS attacks against WLAN throughput. The results of implementation of our experiments shows that how easily DoS attacks can be performed on WLAN which causes to reduce throughput of communication considerably to make inaccessible wireless connection for its authorized members.